New Horizons in Short Children Born Small for Gestational Age - Netchine, Irène; van der Steen, Manouk; López-Bermejo, Abel; Koledova, Ekaterina; Maghnie, Mohamad (Frontiers in Pediatrics, 2021)
Children born small for gestational age (SGA) comprise a heterogeneous group due to the varied nature of the cause. Approximately 85-90% have catch-up growth within the first 4 postnatal years, while the remainder remain short. In later life, children born SGA have an increased risk to develop metabolic abnormalities, including visceral adiposity, insulin resistance, and cardiovascular problems, and may have impaired pubertal onset and growth. The third ‘360° European Meeting on Growth and Endocrine Disorders’ in Rome, Italy, in February 2018, funded by Merck KGaA, Germany, included a session that examined aspects of short children born SGA, with three presentations followed by a discussion period, on which this report is based. Children born SGA who remain short are eligible for GH treatment, which is an approved indication. GH treatment increases linear growth and can also improve some metabolic abnormalities. After stopping GH at near-adult height, metabolic parameters normalize, but pharmacological effects on lean body mass and fat mass are lost; continued monitoring of body composition and metabolic changes may be necessary. Guidelines have been published on diagnosis and management of children with Silver-Russell syndrome, who comprise a specific group of those born SGA; these children rarely have catch-up growth and GH treatment initiation as early as possible is recommended. Early and moderate pubertal growth spurt can occur in children born SGA, including those with Silver-Russell syndrome, and reduce adult height. Treatments that delay puberty, specifically metformin and gonadotropin releasing hormone analogs in combination with GH, have been proposed, but are used off-label, currently lack replication of data, and require further studies of efficacy and safety.